The Decision to Use E-Wallet in The Millennial Generation in Jakarta - Franky Okto Bernando; Erick Lauren Ray (AIBPM Publisher, 2023)
This study aims to analyze the effect of Environmental Consciousness, Perceived Usefulness, and Perceived Ease of Use on the Decision to use E-Wallet in the Millennial Generation in Jakarta through their Attitude Toward Green. It is hoped that through this research, you can see the extent to which technology is utilized with the UTAUT Model and Millennial Generation Purchase Behavior in Jakarta in the use of digital technology in supporting green behavior attitudes. The sampling method used is purposive sampling. This research was conducted using the questionnaire method, conducted on 190 respondents. Quantitative analysis includes validity and reliability tests, classical assumption tests, coefficient of determination R2, F test, t-test and multiple regression analysis. The R2 value of 0.357 indicates that 35.7% of the achieved use decisions are indeed influenced by the independent variables used in this study. From these findings, we will determine the effect of Perceived Usefulness, Environmental Consciousness and Perceived Ease of Use on the Decision to Use E-Wallet with an Attitude Toward Green as an intervening variable in the millennial generation in the city of Jakarta so that later it will be able to contribute thoughts related to the study of attitude toward green or financial technology.